In search of new identities: the DOD and CIA from the end of the Cold War through the Global War on Terror - Oakley, David Patrick (Kansas State University, 2016)
Since September 11, 2001, the CIA and DoD have operated together in Afghanistan, Iraq, and during counterterrorism operations. Although the Global War on Terrorism gave the CIA and DoD a common purpose, it was actions taken in the late eighties and early nineties that set the foundation for their current relationship. Driven by the post-Cold War environment and lessons learned during military operations, policymakers made intelligence support to the military the Intelligence Community’s top priority. In response to this demand, the CIA/DoD instituted policy and organizational changes that altered the CIA/DoD relationship. While debates over the future of the Intelligence Community were occurring on Capitol Hill, the CIA and DoD were expanding their relationship in peacekeeping and nation-building operations in Somalia and the Balkans. By the late 1990’s, some policymakers and national security professionals became concerned that intelligence support to military operations had gone too far, weakening the long-term analysis required for strategy and policy development. Despite these concerns, no major changes to either national intelligence organizations or its priorities were implemented. These concerns were forgotten after 9/11, as the United States fought two wars and policymakers increasingly focused on tactical and operational actions. As policymakers became fixated with terrorism and the United States fought in Iraq and Afghanistan, the CIA focused a significant amount of its resources towards global counterterrorism efforts and in support of military operations. The CIA/DoD operational relationship has led to successes such as the raid that killed Osama Bin Laden, but CIA’s counterterrorism and military support requirements have placed a significant burden on the organization. As the United States’ only independent intelligence organization, the CIA was conceived to separate the collection of intelligence from the institutions that develop and execute policy. The CIA’s increased focus on support to military and counterterrorism operations weakens this separation, reduces its focus on strategic issues, and risks subordination to the DoD. The CIA and DoD are the ones immediately affected by this evolving relationship, but it is policymaker preference for military force and the militarization of foreign policy that has led both organizations down this path.
Keywords: Military; Intelligence